Prox1 identifies proliferating neuroblasts and nascent neurons during neurogenesis in sympathetic ganglia. Issue 12 (20th June 2015) - Holzmann, Julia; Hennchen, Melanie; Rohrer, Hermann
ABSTRACT: Neurogenesis in embryonic sympathetic ganglia involves neuroblasts that resume proliferation following neuronal differentiation. As cell cycle exit is not associated with neuronal differentiation, the identity of proliferating neuroblasts is incompletely understood. Here, we use sympathetic ganglia of chick embryos to define the timing of neurogenesis and neuroblast identity focusing on the expression and function of the transcription factor Prox1. We show that a large fraction of neuroblasts has initially withdrawn from the cell cycle at embryonic day 3 (E3), which is reflected by a high proportion of p27 + /Islet1 + neuroblasts (63%) and low numbers of EdU + /Islet1 + cells (12%). The proportion of proliferating Islet1 + neuroblasts, identified by EdU pulse labeling and by the absence of the postmitotic marker p27 increases to reach maximal levels at E5, when virtually all neuroblasts are in the cell cycle (95%). Subsequently, the proportion of EdU‐labeled and p27 − neuroblasts is reduced to reach low levels at E11. Interestingly, the expression of the transcription factor Prox1 is restricted to the neuronal lineage, that is, Sox10 + /Phox2b + neuron progenitors, proliferating p27 − /Islet1 + neuroblasts and nascent neurons but is rapidly lost in postmitotic neurons. In vitro and in vivo knockdown and overexpression experiments demonstrate effects of Prox1 in the support of neuroblast proliferation and survival. Taken together, these results define the neurogenesis period in the chick paravertebral sympathetic ganglia including an initial cell cycle withdrawal and identify Prox1 as a marker and regulator of proliferating sympathetic neuroblasts. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 75: 1352–1367, 2015